Ответы и объяснения

2013-10-24T23:56:55+04:00
1) \sqrt[9]{x^{4}}  / \sqrt[18]{x^{11}} =  \sqrt[18]{x^{8}}  / \sqrt[18]{x^{11}} =x^{8}  / x^{11} = x^{8/11}

2) 2* \sqrt[4]{16*0.0625}
(0.0625= \sqrt{0.25}  =  \sqrt{1/4}  = (1/4)^{-2}
16 *(1/4)^{-2} =(64/4)*(1/4)^{-2} = (64/4)*(4/1)^{2} = (64*16/1) =1024
2 \sqrt[4]{1024}  = sqrt[4]{1024* 2^{4} }=sqrt[4]{1024* 4*4 }=8 \sqrt[4]{4}

3)№1
 \sqrt{4-3x}=x 


 \sqrt{4} - \sqrt{3x}=x
\sqrt{4}=x+\sqrt{3x}
\sqrt{4} = \sqrt{ x^{2}+3x }
 x^{2}  +3x -4=0

3)№2
\sqrt{7+x} -\sqrt{3-x}=2
\sqrt{7+x-3+x}= 2
\sqrt{4+2x}=2
\sqrt{2x}=0
если вы не учили неопределенность, то x=0

4)  \sqrt[13]{ b^{4}* \sqrt[3]{b}  } = \sqrt[13]{b^{4}* b^{-3} } = \sqrt[13]{b} =b^{-13}